Optimizing the Implementation of Deep Learning in Elementary School Learning at SDN Pampang, Makassar City: Penelitian - Burhan Burhan; Nurwidyayanti Nurwidyayanti; Achmad Fajar Muhammad; Andi Agusniati; Rahmat S. Bintang (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The deep learning approach in education emphasizes the importance of comprehensive conceptual understanding through the active engagement of students in the learning process. This approach is not only oriented toward mastering subject matter but also toward developing critical and reflective thinking skills, as well as the ability to connect knowledge with real-life experiences. However, in practice, the implementation of learning that promotes deep understanding still faces several challenges, such as the dominance of teacher-centered instruction and the limited use of learning strategies that encourage active student participation. This study aims to analyze the optimization of deep learning implementation in the learning process at SDN Pampang, Makassar City. The research employed a qualitative approach using a case study method. The research informants consisted of the school principal, six classroom teachers, and eighteen students from grades IV, V, and VI. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The results indicate that the implementation of deep learning at SDN Pampang is carried out through the integration of three main dimensions: meaningful learning, mindful learning, and joyful learning. Teachers connect learning materials with students’ real-life experiences to create more contextual learning. In addition, teachers encourage students to reflect on their learning processes and create an active and enjoyable learning environment. This implementation has been shown to increase student engagement in the learning process and help them understand concepts more deeply. Therefore, optimizing deep learning can be an effective strategy for improving the quality of learning in elementary schools.